Lung microbiota of patients with ARDS due to coronavirus disease 2019 receiving ECMO - Yumi Mitsuyama; Kentaro Shimizu; Daisuke Motooka; Hiroshi Ogura; Satoshi Fujimi; Jun Oda (Scientific Reports)
Abstract Diversity of the microbiota, which is essential for lower airway homeostasis, is greatly altered in acute respiratory distress syndrome (ARDS). Extracorporeal membrane oxygenation (ECMO) is the ultimate protective treatment for the lungs of patients with severe ARDS, but little is known about its effect on the lung microbiota of these patients. To evaluate the effect of ECMO on the lung microbiota of ARDS patients, we performed 16S rRNA and fungal ITS1 profiling and shotgun sequencing on bronchoalveolar lavage fluid (BALF) collected from ARDS patients due to COVID-19. BALF was collected from 13 patients, five of whom underwent ECMO. In all patients, Pseudomonas was the most abundant of the bacteria. The patients with ECMO had more Pseudomonas and more Klebsiella than those without ECMO. The most abundant fungi were unspecified fungi in the patients with ECMO and Emmia lacerata in the patients without ECMO. Alpha diversity of bacteria and fungi did not differ significantly between the two groups. Human betaherpesvirus 5 and human alphaherpesvirus 1 were predominant in all patients, with human betaherpesvirus 5 decreasing over time in the ECMO patients. The patients with ARDS due to COVID-19 receiving ECMO had a different lung microbiota than those not receiving ECMO.